2021
DOI: 10.1186/s12889-021-10531-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of negative emotional eating and its associated psychosocial factors among urban Chinese undergraduates in Hong Kong: a cross-sectional study

Abstract: Background Emotional eating (EE), defined as eating in response to a range of emotions, has been previously associated with poor diet and obesity. Since there are limited data from non-Western populations, this study aims to examine the prevalence and factors associated with EE among urban Chinese university students. Methods A cross-sectional study was conducted on 424 university students (aged 18–24 years) from two large universities in Hong Kong… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 56 publications
4
26
0
3
Order By: Relevance
“…In our study, the emotional eating score was strongly associated with depressive symptoms, which is in line with data from other authors, showing a relationship between EE and negative emotions and perceived stress [ 56 , 90 , 91 ]. In our sample, emotional eaters more often consumed sugar, sweets and snacks, consistent with previous reports [ 43 , 92 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the emotional eating score was strongly associated with depressive symptoms, which is in line with data from other authors, showing a relationship between EE and negative emotions and perceived stress [ 56 , 90 , 91 ]. In our sample, emotional eaters more often consumed sugar, sweets and snacks, consistent with previous reports [ 43 , 92 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our sample, emotional eaters more often consumed sugar, sweets and snacks, consistent with previous reports [43,92]. Moreover, we confirmed previous results on the associations of emotional eating with higher BMI [56,79,80,82,83,89,90].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, female respondents were found to be more prone to emotional eating, compared to males. This result is in compliance with other studies [48,58,59] which have indicated that women are especially susceptible to eating in response to negative emotions. The study of Péneau et al [48] highlighted that French adult women more likely engaged in emotional eating than men.…”
Section: Discussionsupporting
confidence: 93%
“…The study of Péneau et al [48] highlighted that French adult women more likely engaged in emotional eating than men. Similarly, the study by Sze et al [58], which was carried out among Chinese university students, revealed that women were characterized by about threefold higher likelihood of emotional eating than men. Additionally, in the study by Camilleri et al [59], which analyzed the association between emotional eating and intake of energy-dense snacks, such association was observed to be stronger in women with depressive symptoms, compared to men with depressive symptoms.…”
Section: Discussionmentioning
confidence: 82%
“…The interventions proposed in the included studies can be divided into two broad categories: social support and coping strategies. Social support was provided by government authorities [ 49 , 52 - 54 , 61 , 62 , 68 , 72 , 84 , 86 - 88 ]; university authorities [ 12 , 48 , 50 , 51 , 53 - 55 , 57 - 59 , 62 , 64 , 65 , 67 , 69 , 91 , 93 ]; students’ affairs counselors and teachers [ 54 , 75 , 83 - 85 , 87 , 93 ]; family members [ 52 , 54 , 57 , 83 , 94 ]; health care authorities and professionals [ 52 , 63 , 66 , 75 , 77 - 79 , 87 ]; researchers [ 70 , 85 ]; and media-, internet-, and smartphone-based interventions [ 26 , 53 , 55 , 56 , 60 , 71 , 73 , 75 , 77 , 80 , 81 ]. Positive coping strategies were adopted by undergraduate students themselves [ 52 , 82 , 83 , 85 , 86 ,…”
Section: Resultsmentioning
confidence: 99%